Clinical Case Analysis of CT Diagnosis of Bilateral Adrenal Diffuse Hemorrhage - Huimei CHEN; Lingling ZHANG; Rengui WANG (CT Lilun yu yingyong yanjiu)
Bilateral adrenal diffuse hemorrhage (BADH) is a rare hemorrhagic disease due to multiple causes, and the clinical manifestations are principally non-specific abdominal and thoracic pain. Due to its rarity, early detection and diagnosis of BADH can be challenging for physicians. We reported two cases of BADH, both of which are severe systemic lupus erythematosus (SLE) complicated with adrenal hemorrhage. The first case report was a 26-year-old female patient who presented with progressive worsening abdominal pain, nausea, vomiting, fever and multi-organ functional involvement. Abdominal CT scan revealed diffuse thickening of the adrenal glands and serous cavity effusion. The comprehensive assessment of the clinical findings suggested that it was a secondary change of severe SLE involving multiple systems. The second case was a 58-year-old female patient with SLE who occurred abdominal pain 2 days after admission. CT scan of abdomen revealed a retroperitoneal hematoma, and a subsequent contrast-enhanced ultrasound confirmed the adrenal hemorrhage. After active treatment of primary diseases, along with symptomatic and conservative treatments, the symptoms of patients were significantly relieved, and reexamination of abdominal CT scan showed obvious absorption of the lesion. This report provides a comprehensive introduction to BADH, summarizes its CT features and clinical symptoms to improve physicians’ understanding of BADH and provide some aids and references for its early diagnosis.